A poiesis of peace: imagining, inventing & creating cultures of peace. The qualities of the artist for peace education. Issue 2 (4th May 2021) - Lehner, Daniela
ABSTRACT: In this theoretical article, the qualities of the artist for peacebuilding and peace education are explored. Peacebuilding and peace education are not only based on skills and knowledge, but also on art, a creative process that originates in our imagination. The question guiding this paper is: How can we, as peacebuilders and educators, imagine, invent, and create cultures of peace and build spaces for others to do so? Based on Lederach's moral imagination, I present a conceptualization of a poiesis of peace as a frame for peace education. This so-called poiesis of peace is built on the sensibility of the heart as the feeling center that can perceive the imaginal and the relationality of breath as described by Irigaray as a field of intersubjectivity and interconnectedness. The potential of this imaginative sensibility is the ability to feel into another experience, described as empathy and resonance, which might manifest as an ethics of care and nonviolence. Using arts based methods in peace education can be one way to encourage feelings of interconnectedness and empathy.